Chemical Constituents of the Essential Oils from Flower, Leave and Stem of the Salvia brachycalyx Boiss. from Iran - HADI MESHKATALSADAT, MOHAMMAD; ASADI, MAHBOBEH (Asian Journal of Chemistry, 2010)
The water-distilled essential oil produced from different parts of Salvia brachycalyx Boiss., endemic in Iran, was analyzed by GC/MS. 27 Compounds have been identified and the major components include geraniol, benzyl benzoate, spathulenol, 1,8-cineole and citral.